Media use during adolescence: the recommendations of the Italian Pediatric Society - Elena Bozzola; Giulia Spina; Margherita Ruggiero; Davide Vecchio; Cinthia Caruso; Mauro Bozzola; Anna Maria Staiano; Rino Agostiniani; Antonello Del Vecchio; Giuseppe Banderali; Diego Peroni; Alberto Chiara; et al. (BMC, 2019)
Abstract Background The use of media device, such as smartphone and tablet, is currently increasing, especially among the youngest. Adolescents spend more and more time with their smartphones consulting social media, mainly Facebook, Instagram and Twitter because. Adolescents often feel the necessity to use a media device as a means to construct a social identity and express themselves. For some children, smartphone ownership starts even sooner as young as 7 yrs, according to internet safety experts. Material and methods We analyzed the evidence on media use and its consequences in adolescence. Results In literature, smartphones and tablets use may negatively influences the psychophysical development of the adolescent, such as learning, sleep and sigh. Moreover, obesity, distraction, addiction, cyberbullism and Hikikomori phenomena are described in adolescents who use media device too frequently. The Italian Pediatric Society provide action-oriented recommendations for families and clinicians to avoid negative outcomes. Conclusions Both parents and clinicians should be aware of the widespread phenomenon of media device use among adolescents and try to avoid psychophysical consequences on the youngest.